Implementation of Virtual Reality in Preclinical Pediatric Dentistry Learning: A Comparison Between Simodont® and Conventional Methods - Antonia M. Caleya; Andrea Martín-Vacas; María Rosa Mourelle-Martínez; Manuel Joaquín de Nova-Garcia; Nuria E. Gallardo-López (Dentistry Journal)
Background/Objectives: Preclinical training in pediatric dentistry is traditionally performed on acrylic primary teeth or natural extracted teeth in phantoms or dental manikins. With technological advancements, virtual simulation has become increasingly common, enhancing the development of cognitive and motor skills in dental students while complementing traditional methods. Specific objectives included assessing whether preclinical theoretical knowledge impacts motor skill scores, comparing the quality of dental preparations on acrylic teeth versus those performed using virtual simulation (Simodont®) and evaluating students’ perceptions of Simodont® use. Methods: An observational, descriptive, cross-sectional study was conducted. Students first completed a theoretical knowledge survey on dental preparations, class II caries, and pulpotomies. They then performed dental preparations on both acrylic primary teeth and the Simodont® simulator, with their work assessed by a pediatric dentistry professor. Finally, students completed a perception survey regarding their experience. Results: The introduction of the Simodont® was positively received. Theoretical knowledge prior to preclinical exercises did not significantly influence practice scores. Average scores for preparations on acrylic teeth (class II: 2.57; pulpotomy: 3.60) were higher than those achieved using Simodont® (class II: 1.97; pulpotomy: 2.92). Conclusions: Dental preparation scores were higher on acrylic teeth compared to the virtual simulation. While students reported a positive experience with Simodont®, they expressed a preference for traditional learning methods involving acrylic teeth on phantoms or dental manikins.